Efek Aquatic Aerobic Activity Terhadap Perkembangan Kemampuan Basic Motor Control, Gross Motor Dan Occupational Performance Skills Pada Anak Cerebral Palsy (CP) - Hendri Kurniawan; Erayanti Saloko (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Aquatic Aerobic Activity, Land Based Activity, Motor Control. Cerebral palsy (CP) is characterized by sensorimotor disorders of motor control (gross motors and fine motor) as well as posture. Aquatic aerobic activity is designed to give sensorimotor stimulation through a series of activities undertaken in the pool. Indicators of sensorimotor function improvement in CP can be evaluated through changes in the motion control capabilities, basic motor control in the setting of functional posture, and the ability to perform functional activities. The purpose of this study was to examine the effect of aerobic aquatic activity towards the development of motor abilities, basic motor control, and occupational performance skills in children with CP. The study design was performed according to quasi-experimental design with control group pretest-posttest design. The study population was patients with CP that received rehabilitation treatment in occupational therapy unit YPAC Surakarta. Sampling using quota sampling with a sample size of 30 people. Analysis of data using paired samples t-test, Wilcoxon and Mann-Whitney using SPSS version 16.0. The average value of the change scores Bobath Chart and GMFM post-intervention aquatic aerobic activity amounted to 4.07 and 7.33, while the post-intervention land-based activity amounted to 0.80 and 1.53. The test results paired sample t-test for Bobath Chart scores and GMFM scores before and after intervention showed p-value <0.05. The results of the comparative analysis showed a significant difference (p-value <0.05) between the changes Bobath Chart scores and GMFM scores between the intervention group aquatic aerobic activity with land-based activity. Performance and satisfaction scores increased by 0.13 and 0.47 (aquatic aerobic activity) and 0.07 & 0.27 (land-based activity). Aquatic Aerobic Activity results in significant effect towards basic motor control, gross motor and occupational performance skills in children with CP.